Preparation of Photoactive Zns-Composite Porous Polymer Films: Fluorescent and Morphological Properties - Sanchez-Poblete, J (Taylor and Francis Ltd., 2021)
This work describes the use of the breath figure (BF) method for the fabrication of photoactive porous polymer films and the characterization of their responsive to photo stimulus. The films incorporate self-assembled photoactive polymers and ZnS nanoparticles (NPs). The effect of both components on the optical and morphological properties of the films were analyzed. Films with a hexagonally ordered pattern were obtained. The photoactive polymer was prepared by grafting the photochromic component 1-(2-hydroxyethyl)-3,3-dimethylindoline-6-nitrobenzopyran (SP) to polystyrene-block-polymethacrylic acid (PS-b-PMMA). ZnS NPs were incorporated into the polymer solution, and the films were prepared using spin-coating on glass substrates before subjecting them to the BF method. The hollow footprints were obtained before introducing the ZnS NPs in order to maintain the necessary conditions for hexagonal film growth. Accordingly, the SEM micrographs of the films prepared in the presence of ZnS NPs displayed a loss in the pore arrangement as a consequence of the interaction between SP moiety and NPs. The light-emitting properties of films were characterized by blue and violet colors when exposed to UV light under fluorescence. Progress in the field of breath-figure formation and its application, such as exemplified in this work, leads to functional structures with suitable applications in chemistry and materials science. It is expected that such microstructured polymeric films will have interesting applications in photonic and optoelectronic devices. © 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.